Echinococcus multilocularis Detection in Live Eurasian Beavers (Castor fiber) Using a Combination of Laparoscopy and Abdominal Ultrasound under Field Conditions - Campbell-Palmer, Róisín (PLoS One, 2015)
Echinococcus multilocularis is an important pathogenic zoonotic parasite of health concern, though absent in the United Kingdom. Eurasian beavers (Castor fiber) may act as a rare intermediate host, and so unscreened wild caught individuals may pose a potential risk of introducing this parasite to disease-free countries through translocation programs. There is currently no single definitive ante-mortem diagnostic test in intermediate hosts. An effective non-lethal diagnostic, feasible under field condition would be helpful to minimise parasite establishment risk, where indiscriminate culling is to be avoided. This study screened live beavers (captive, n = 18 or wild-trapped in Scotland, n = 12) and beaver cadavers (wild Scotland, n = 4 or Bavaria, n = 11), for the presence of E. multilocularis. Ultrasonography in combination with minimally invasive surgical examination of the abdomen by laparoscopy was viable under field conditions for real-time evaluation in beavers. Laparoscopy alone does not allow the operator to visualize the parenchyma of organs such as the liver, or inside the lumen of the gastrointestinal tract, hence the advantage of its combination with abdominal ultrasonography. All live beavers and Scottish cadavers were largely unremarkable in their haematology and serum biochemistry with no values suspicious for liver pathology or potentially indicative of E. multilocularis infection. This correlated well with ultrasound, laparoscopy, and immunoblotting, which were unremarkable in these individuals. Two wild Bavarian individuals were suspected E. multilocularis positive at post-mortem, through the presence of hepatic cysts. Sensitivity and specificity of a combination of laparoscopy and abdominal ultrasonography in the detection of parasitic liver cyst lesions was 100% in the subset of cadavers (95%Confidence Intervals 34.24–100%, and 86.7–100% respectively). For abdominal ultrasonography alone sensitivity was only 50% (95%CI 9.5–90.6%), with specificity being 100% (95%CI 79.2–100%). For laparoscopy alone sensitivity was 100% (95% CI 34.2–100%), with specificity also being 100% (95% CI 77.2–100%). Further immunoblotting, PCR and histopathological examination revealed one individual positive for E. multilocularis, whilst the other individual was positive for Taenia martis.